Catalytic upgrading of the polymeric constituents in Covid-19 masks. Issue 1 (February 2022) - Ali, Labeeb; Kuttiyathil, Mohamed Shafi; Altarawneh, Mohammednoor
Abstract: A substantial volume of various types of Covid-19 masks has been disposed of since the start of the global pandemic. These facemasks are made of non-degradable polymeric materials. As such, they currently signify a major source of microplastic pollution in the environment. Through incineration or pyrolysis, thermal processing has emerged as a mainstream approach in the waste management of the ever-increasing loads of generated facemasks. Via a combined experimental-theoretical framework, we report herein salient features that govern thermal decomposition of the distinct plastic-based components in 3 M N95 (with a respirator) and surgical facemasks. Protective three-four layers in the considered masks are composed of polypropylene (PP) that degrades in a one-step across the temperature window 330 – 480 °C. Char residues from the decomposition of ear straps (consisting of polyester) attain 24% and 15% fractions of the initial mass in the case of surgical and N95 masks, respectively. Thermo kinetic parameters are derived for the different components of the facemask by using the Coats-Redfern approach from the thermogravimetric analysis data. Here we also report the potentiality of producing value-added products from the face mask using the GCMS by virtue of the catalytic oxidation of the material expending the Niobium doped CeO2 catalyst under controlled conditions. Constructed mechanisms through density functional theory (DFT) computations illustrated the nature of chemical reactions that mark the two-stage decomposition curve of polyurethane (the material used in the nose area in N95 masks). These chemical events characterize rupture of C-C(O) bonds, sequential departure of CO2 /C2 H4 molecules, and fission of the C-C linkages. Outcomes from this investigation provide important information (i.e., thermal stability regions of the deployed polymers and potential emission profiles) needed in the urgent pursuit to safely and economically recycle polymeric constituents in Covid-19 masks, and potentially other types of medical wastes. Graphical Abstract: ga1 Highlights: The study reports degradation profiles of polymeric constituents in covid-19 masks. FTIR analysis identity the major polymeric fractions in these masks. Degradation of nose foam in N95 masks exhibit two-stage profile with no char formation. DFT computations established opening reactions in the decomposition of N-polymers. Catalytic upgrading by CeO2 -Nb catalyst increases the yield of methylated benzene compounds.